Not in My Backyard: Personal Politics and Resident Attitudes toward Tourism. (April 2020) - Litvin, Stephen W.; Smith, Wayne W.; McEwen, William R.
This research looks at the relationship between political libertarianism and personal self-interest, as informed by the concept of NIMBYism (not-in-my-backyard) that underlies much of the resident attitude toward tourism literature. Based on a comprehensive survey of more than 500 residents from Charleston, South Carolina, a city heavily dependent on tourism, the research determined, as the literature would predict, that general views toward tourism were highly dependent on where one lives. However, for specific tourism issues, one's personal political views tended to trump geography. Application of theory and suggestions for tourism policy makers are provided.